Hadith #4990 - Sunan Abi Dawud - Abu Hurairah; Ali bin Hafs al-Mada'ini علي بن حفص المدائني; Hafs bin 'Asim bin 'Umar حفص بن عاصم بن عمر; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Khbyb bin 'Abdur Rahman خبيب بن عبد الرحمن بن خبيب; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Woe to him who tells things, speaking falsely, to make people laugh thereby. Woe to him! Woe to him!.
Grade: Hasan